Impedance imaging for inhomogeneities of low volume fraction - Capdeboscq, Y (2006)
We first review some recent representation formulas for the boundary voltage perturbation arising as a result of the presence of low volume fraction inhomogeneities, and then discuss the attainability of the limit set of possible polarization tensors by simply connected domains.